Kepemimpinan Kiai Nahdlatul Ulama; Strategi Visioner untuk Optimalisasi Manajemen Pesantren di Lumajang - Ahmad Nawawi Efendi; Revi Rusdatul Jannah; Zulfida Aulia Fatimah (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
Explores the visionary leadership practices of Nahdlatul Ulama (NU) Kiais in transforming the pedagogy and student (santri) character across four pesantren in Lumajang Regency. The central focus is how pesantren leadership responds to the disruption of modernization without losing the essence of Islamic education rooted in Ahlussunnah wal Jama'ah (Aswaja) values. Employing a qualitative case study design with an educational ethnography approach, data were collected through participatory observation of daily rituals and learning cultures, in-depth interviews with key figures, and institutional document analysis. The findings indicate that the Kiais' visionary leadership transcends managerial efficiency; it manifests as an educative force that transforms spiritual awareness, moral discipline, and adaptive learning culture (deep learning) through the internalization of the ta’dib tradition. The resulting enhancement in institutional performance is fundamentally a secondary impact of the Kiais' success in positioning themselves as murabbi (spiritual educators) who nurture a moderate and inclusive worldview among the santri. The novelty of this research lies in the construction of a transformative Islamic educational leadership model, proving that the integration of Aswaja's pedagogical philosophy with digital-vocational innovation is the core foundation for pesantren resilience. This study concludes that the Kiais' visionary leadership is crucial in preserving the authenticity of the pesantren while simultaneously shaping a Muslim generation adaptive to global dynamics.